Identification, distribution and ultramorphology of the larvae of Gynaephora menyuanensis (Lepidoptera: Lymantriinae) endemic to Qinghai-Tibet plateau - Chen Yuan; Yunxiang Liu; Hainan Shao; Jinping Fu; Siyu Liu (Scientific Reports)
Abstract The grassland caterpillar is a significant pest of alpine meadows on the Qinghai-Tibet Plateau. Its larvae primarily feed on forage grasses, resulting in financial losses. However, limited research has been done on the morphological features of larvae of this species thus far. The distribution and habitat of Gynaephora menyuanensis were extensively investigated in this instance through field study. The findings indicate that this species is primarily found in the northeast of Qinghai and parts of Gansu Province in alpine meadows at an altitude of 3,000 m. For the first time, SEM is used to report the external morphology and ultramorphology of the first and last instar larvae of G. menyuanensis, including the larval head capsule, mouthparts, antennae, sensilla, thoracic legs, prolegs, and setae. The results indicated that the larvae share similar morphological characteristics except for the number of cutting incisors and crochets. The mature instar larvae have two distinct color funnel warts (yellow and red) on abdominal segments VI and VII, distinguishing them from other lepidopteran larvae. Additionally, the chaetotaxy of the first instar larvae of G. menyuanensis was studied and described in detail, identifying seven clusters (PD, D, SD, L, SV, V, CV) on the larval trunk. This study provides a theoretical basis for the rapid identification of such pests and is beneficial for their monitoring and management.